Merdeka Belajar Kampus Merdeka: Tantangan dan Prospek Kedepan - Uswatun Hasanah (Kopertais Wilayah XV Lampung, 2022)
Merdeka Belajar-Kampus Merdeka (MBKM) basically has four important components, such as the ease of creating new study programs, changes to the accreditation system, the ease of becoming Perguruan Tinggi Badan Hukum (PTN-BH) or a Legal Higher Education, and providing students with the right to study outside the campus within eight learning programs. This transformative and innovative policy in fact has some problems and challenges that hinder the implementation of MBKM. Therefore, this study aims to examine the challenges and prospects of MBKM policies. This research is a library research with analytical techniques using content analysis and library sources related to the research problems. The results show that the challenges of MBKM are that the MBKM policy has not been fully accepted, the lack of socialization of the credit score assessment mechanism (SKS) with relevant courses, renewal of the LMS and internship mechanism, collaboration between agencies, and PTN-BH problems. Therefore, MBKM will be able to be implemented effectively and comprehensively if various parties are highly committed to do their best, including educational institutions, lecturers, students, as well as the Government that work together to support the implementation of various programs in MBKM to create better human resources and characteristics.